The impact of the Covid19 pandemic on social and regional differences in the sports behaviour of the Swiss population - Rahel Bürgi; Markus Lamprecht (Bern Open Publishing, 2023)
The Covid19 pandemic and the accompanying measures between March 2020 and March 2022 had a strong impact on the sport system. The various restrictions on sports activities affected not only school sports, but also clubs and fitness centres, as well as competitive sports in general. At the same time, a considerable increase in unorganised outdoor sports activities and a shift in sport preferences could be observed. In order to assess and quantify the short- to medium-term changes in the sporting behaviour of the Swiss population due to the Covid 19 pandemic, the Federal Office of Sport commissioned a representative population survey. For this purpose, 2,130 people aged 15 and over were surveyed in the summer of 2022 in the three national languages German, French and Italian by means of an online questionnaire. To facilitate comparisons over time, the survey was based on the survey instrument of the "Sport Switzerland" studies (cf. Lamprecht et al., 2020), with additional questions on the assessment and management of the Covid19 pandemic. For the present paper, on the one hand, results on the changes in sports behaviour during the Covid19 pandemic will be presented and it will be shown how these changes affected sports activity in the different settings in the medium term. On the other hand, the consequences of these changes on social and regional differences in sports behaviour (cf. Lamprecht & Nagel, 2022) will be examined. Did the Covid19 pandemic and the accompanying measures in the field of sport tend to increase or rather level out the differences according to age, gender, social status and place of residence? Did the pandemic lead to a situation in which population groups who were only sparingly and irregularly active in sport were increasingly discouraged from taking part in sport, while those who were more active in sport found it easier to switch to other types of sport and settings? With regard to the regions, it will be investigated whether a connection can be found between compliance with the Corona measures and the changes in sports behaviour. Finally, the question will be raised as to how lasting the measured changes and shifts are likely to be and how an increase in social inequality in the field of sport could be countered.  References Lamprecht, M., & Nagel, S. (2022). Sportsoziologie: Einführung. Nomos. Lamprecht, M., Bürgi, R., & Stamm, H. (2020). Sport Schweiz 2020: Sportaktivität und Sportinteresse der Schweizer Bevölkerung. Bundesamt für Sport BASPO.